2014
DOI: 10.1186/1472-6963-14-s1-s1
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for some but not all: inequity within community health worker teams during introduction of integrated community case management

Abstract: BackgroundThe Ugandan health system now supports integrated community case management (iCCM) by community health workers (CHWs) to treat young children ill with fever, presumed pneumonia, and diarrhea. During an iCCM pilot intervention study in southwest Uganda, two CHWs were selected from existing village teams of two to seven CHWs, to be trained in iCCM. Therefore, some villages had both ‘basic CHWs’ who were trained in standard health promotion and ‘iCCM CHWs’ who were trained in the iCCM intervention. A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This could portray the value the community attaches to biomedical interventions. Indeed, research has shown that CHWs who give drugs or commodities to community members are more respected [36,40]. Norms and community perceptions of illness could also play a part in the high interest in biomedical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This could portray the value the community attaches to biomedical interventions. Indeed, research has shown that CHWs who give drugs or commodities to community members are more respected [36,40]. Norms and community perceptions of illness could also play a part in the high interest in biomedical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Individual, group, and program factors have each been shown to influence the performance of CHVs (1, 3, 5, 6, 815, 1719, 25). Factors previously reported to result into improved performance include the female gender, regular supervision and provision of feedback, higher education, the availability of job aides and other tools, and feeling “connected” with the system (3, 5, 6, 911, 13, 14, 17, 18). …”
Section: Discussionmentioning
confidence: 99%
“…However, the findings have been heterogeneous and influenced by many factors (4, 8), including socio-demographic, political, economic, and workplace environments. Workload, attrition rates, gender roles, level of education, political commitment and employment status, job aides, and physical workplace environment have a significant influence on such workers’ performance (36, 915). Understanding the contextual factors and enablers that influence the performance of CHVs is relevant for many settings aiming to use them to achieve the SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…Together, Mbarara University of Science and Technology (Uganda), the University of Calgary (Canada) and the Canadian Paediatric Society promote health system strengthening in rural districts using MNCH as an entry point. Through research, HCU has sought to better understand factors related to effective implementation and sustainability of related programming [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%